(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article illustrates the important influence of oriental literature on the development and prosperity of the Chinese modern Kazakh literature. This article essential influence of east literature on development and prosperity of the Chinese modern Kazakh literature is shown. And to article it is shown as to develop Kazakh poetry in China and as it influences, and in China the Kazakh poets use tradition "nazira". The tradition "nazira" influences on the Kazakh written literature in China. Poets used this tradition to compose the creativity. Also it is tradition I influenced the poet to seem at top.